Elaboration of multivariate model for prediction early lethal outcome after spontaneous supratentorial intracerebral hemorrhage using parameters of computer tomography - Kuznietsov, A. A.; Krilov, A.; Кузнєцов, Антон Анатолійович (Запорізький державний медичний університет, 2016)
Background: Elaboration of statistical models to predict early lethal outcome (ELO) after spontaneous supratentorial intracerebral hemorrhage (SSICH) is a very important and relevant in modern angioneurology that can help the practicioners to identify candidates for neurosurgical intervention and improve effectiveness of treatment approaches. We therefore elaborated new statistical for prediction ELO after SSICH using parameters of computer tomography (СT).